Predictive value of neutrophil-to-lymphocyte ratio before the second biopsy while detecting atypical small acinar proliferation (Annals of Medical Research, 2021)
Aim: In this study, we aimed to detect of predictive valueof neutrophil-to-lymphocyte ratio before the second biopsy while detecting atypical small acinar proliferation (ASAP) in high prostate-specific antigen (PSA) level.Material and Methods: Two thousand two hundred ninety five patients underwent 10-12 quadrant TRUSBP between January 2008 and January 2016 have been evaluated retrospectively. Seventy sixpatients, whose data were reached, are taken into the study. Before the first biopsy,total PSA (tPSA), free PSA (fPSA), rate of percentage of free to total prostate specific antigen (f/tPSA) rate, PSA density (PSAD),blood neutrophil count (NC) and neutrophil-to-lymphocyte ratio (NLR)were measured. Second biopsy results and changes in the data are compared.Results: Benign prostate hyperplasia in 44 patients (57.89%),ASAP in 16 (21.05%) and prostate adenocarcinoma (PCa) in 16 patients (21.05%)was detected. The patient’s age, tPSA, fPSA, t/fPSA, PSAD,NC and NLR were 63.29 years, 8.68ng/mL, 1.87ng/mL, 21.34%, 18.15 ng/ml2, 5.2710^3/μL and 2.95 in group 1 and 64.31 years, 8.62 ng/mL, 1.58ng/mL,21.01%, 20.18 ng/ml2, 7.5310^3/μL and 2.84 in group 2, respectively. Patient’s age, tPSA, fPSA, f/tPSA, PSAD, NC and NLR were not statistically significant between in two groups (p >0,05).Conclusions: We think that inflammation is a stimulant factor for PCa in patients with ASAP. So, before the first biopsy, it may be able to predict a cancer by considering NC and NLR in patients with ASAP. Although not significant, NC and NLR values were found to be higher in ASAP/malign than benign cases in the evaluation of ASAP patients before the second biopsy.Keywords: Prostate Cancer; Atypical Small Acinar Proliferation; Neutrophil-To-Iymphocyte Ratio.
Keywords: Prostate Cancer; Atypical Small Acinar Proliferation; Neutrophil-To-Iymphocyte Ratio.